2019
DOI: 10.1039/c9ta00882a
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancies promoting the electrocatalytic performance of CeO2nanorods as cathode materials for Li–O2batteries

Abstract: A two-step hydrothermal surface engineering strategy was used to tune the concentration of oxygen vacancies of CeO2 nanorods to achieve the best electrochemical performances of Li–O2 batteries, which reduced the overpotential and extended the electrochemical stability of Li–O2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 59 publications
1
61
0
Order By: Relevance
“…At the initial process of discharging, the main peak of Li 2 O 2 (~55.4°) corresponding to a weak peak of Li 2-x O 2 (~56.1°) were detected, which indicated that the Li 2 O 2 was the main discharge product and LiO 2 was the mediate discharge product at the initial stage of discharge. [60,61] When further discharged to 500 mAh g -1 , the peak of Li 2-x O 2 disappeared and the intensity of Li 2 O 2 peak still increased, demonstrating the formation of Li 2 O 2 film. It is worth mentioning that the peak of Li 2-x O 2 reappeared during the initial charging process.…”
Section: Resultsmentioning
confidence: 99%
“…At the initial process of discharging, the main peak of Li 2 O 2 (~55.4°) corresponding to a weak peak of Li 2-x O 2 (~56.1°) were detected, which indicated that the Li 2 O 2 was the main discharge product and LiO 2 was the mediate discharge product at the initial stage of discharge. [60,61] When further discharged to 500 mAh g -1 , the peak of Li 2-x O 2 disappeared and the intensity of Li 2 O 2 peak still increased, demonstrating the formation of Li 2 O 2 film. It is worth mentioning that the peak of Li 2-x O 2 reappeared during the initial charging process.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the influence of oxygen vacancy on the properties of metal oxides catalysts has also been widely studied . Dang and co‐workers proposed to improve the electrocatalytic activity of CeO 2 nanorods as anode material of lithium–oxygen batteries by adjusting the surface oxygen vacancy concentration, and they found that the higher the oxygen vacancy concentration, the better the electrochemical performance . It can be found that oxygen vacancies can be active sites for the deposition of Li 2 O 2 , and also promote charge transfer in the discharge/charge process.…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…[112] Dang and co-workers proposed to improve the electrocatalytic activity of CeO 2 nanorods as anode material of lithium-oxygen batteries by adjusting the surface oxygen vacancy concentration, and they found that the higher the oxygen vacancy concentration, the better the electrochemical performance. [113] It can be found that oxygen vacancies can be active sites for the deposition of Li 2 O 2 , and also promote charge transfer in the discharge/charge process. In addition, Kim and co-workers reported that the oxygen vacancy of MnMoO 4 is conductive to achieving high catalytic activity and reversibility of Li-O 2 batteries.…”
Section: Defect Engineering For Li-o 2 Batteriesmentioning
confidence: 99%
“…This behavior is in line with the experimental observation of a high nucleation power of ceria NPs deposited on graphene based cathodes. [14][15][16][17] In the adsorption process, the surface oxygen vacancy is filled, and the oxidation of Ce + 3 to Ce + 4 takes place.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Among these issues are the effect of the solvent on the morphology and charge transport properties of the discharge product, [2,3] the use of redox mediators (liquid catalysts), [4][5][6][7][8] modifying the porosity of the carbon cathode, [7,8] and the use of noble metals and metal oxide catalysts. [8][9][10][11][12][13] In this work, we focus on ceria (CeO 2 ), a promising catalyst for LOBs, [14][15][16][17] with the aim to shed light on the mechanisms operating in the nucleation of Li 2 O 2 at stoichiometric and reduced ceria surfaces by means of atomistic simulations based on density functional theory.…”
Section: Introductionmentioning
confidence: 99%